Calculating the Linearly Polarized Modes and their Properties in Weakly Guiding Step Index Fibers - Jameel , Rand T.; Salih, Aqeel R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2026)
The modal properties of optical fibers were calculated at core radii (1.45–5.05) µm in 1.20 µm increments. In this work, the calculation was performed at a wavelength of 1.030 µm using the RP Fiber Calculator software (free version 2025). The results demonstrated that when the core radius is comparable wavelength, the fiber supports only the fundamental mode, indicating single-mode operation; whereas larger core radii lead to multimode behavior. The study involved analyzing optical properties of step index fibers with core and cladding refractive indices of = 1.469 and = 1.46, respectively. The computed properties included the cut-off wavelength, effective area, power in the core, effective refractive index, and propagation constant. The results revealed a progressive increase in these properties with increasing core radius. Furthermore, the geometric distribution of the modal intensity profiles was visualized to provide a comprehensive understanding of the mode field structure.